RADIOISOTOPE PRODUCTION PROCESS OPTIMIZATION MO99 - Melani Dewi Lusita; Hj. Latifah, Dra., MM Hj. Latifah, Dra., MM (Jurnal Sistem Informasi, 1997)
One of the utilization of nuclear technology for peaceful purposes is in medicine,namely the use of radioisotopes that have short half-life as a medium to detect thecondition of the patient. from various short-lived radioisotopes, so the currentradioisotope Mo99, it needs to be done by considering various factors influencing theproduction process such radioisotopes. for it, has obtained results of the optimizationof production processes with the addition of service facilities in accordance with thedesired end result.